ANALYSIS OF FACTORS AFFECTING FOREIGN EXCHANGE RESERVES IN INDONESIA, 2005-2020 - Bayu Pamungkas Djamal; Muhammad Yusri Zamhuri; Abd. Rahman Razak (SEAN Institute, 2023)
The aim of this research is to analyze the effect of foreign loans, imports, exports and foreign investment for the foreign exchange reserves' growth in Indonesia during 2005-2020. This research used secondary data which tends to be time-series published by Bank Indonesia, The Ministry of Trade Republic of Indonesia, Central Agency on Statistics Indonesia in the year of 2005-2020. The result of the regression by using ordinary least squares (OLS) method showed that the foreign loans and exports take effect positively to the foreign exchange reserves. It indicates that the increase in foreign loans and exports could affect the foreign exchange reserves in Indonesia during 2005-2020. Otherwise, the interest rate could not affect the foreign exchange reserves in Indonesia during 2005-2020.